A novel parallel feature extraction method using HGAPSO and GLCO based SFTA - Hasan, Md. Junayed; Khan, Nazmul Kabir; Hridi, Navila Alam; Ontora, Fariha Tahsin (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.